2009
DOI: 10.1016/j.nimb.2009.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Possible diamond-like nanoscale structures induced by slow highly-charged ions on graphite (HOPG)

Abstract: The interaction between slow highly-charged ions (SHCI) of different charge states from an electron-beam ion trap and highlyoriented pyrolytic graphite (HOPG) surfaces is studied in terms of modification of electronic states at single-ion impact nanosize areas. Results are presented from AFM/STM analysis of the induced-surface topological features combined with Raman spectroscopy. I-V characteristics for a number of different impact regions were measured with STM and the results argue for possible formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…In many solids, hillocks are induced by SHI at the surface with a radius that depends on the electronic energy loss [4][5][6][7][8]. Similar surface nanostructures were also detected on HCI impacted materials [9][10][11][12]. The similarity among the nanostructures indicates that a common mechanism related to the energy transfer process is involved in both irradiation types.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In many solids, hillocks are induced by SHI at the surface with a radius that depends on the electronic energy loss [4][5][6][7][8]. Similar surface nanostructures were also detected on HCI impacted materials [9][10][11][12]. The similarity among the nanostructures indicates that a common mechanism related to the energy transfer process is involved in both irradiation types.…”
Section: Introductionmentioning
confidence: 71%
“…1a, 1b and 1c. During the irradiation of 479 MeV Kr ions on HOPG, a new peak denoted as D peak (~1338 cm -1 ) appears in addition to the original G peak (~1582 cm -1 ) when the fluence is 5×10 12 ions/cm 2 or higher (insert of Fig. 1a).…”
Section: Irradiation Effects In Hopgmentioning
confidence: 99%
“…As an interesting application it was demonstrated that the defects induced by HCI on HOPG can be transformed by subsequent irradiation with electrons (from the STM tip) or photons (Cd-Te laser) to sp 3 graphite, i.e. to nanoscaled diamond structures [46][47][48]. Recently, these modifications could be found also in simulations of the impact of highly charged Ar ions on graphite using time-dependent density functional theory combined with MD [49].…”
Section: Layered Materialsmentioning
confidence: 99%